Efficient and Reusable Activated Carbon from Aframomum angustifolium Fruits’ Shells for Removal of Ceftriaxone from Aqueous Solution: Adsorption Isotherms, Kinetics, and Thermodynamics Studies - Kasazi, Baraka Alfaksad; Mwakalesi, Alinanuswe Joel; Lema, Emmy Solomon (Indonesian Journal of Chemistry, 2026)
The accumulation of ceftriaxone antibiotics in aquatic systems is a growing global concern due to their potential risks to human and ecological health. The current study investigates the synthesis, characterization, and application of activated carbon (AC-FPAA-H3PO4) made from the shells of Aframomum angustifolium fruits. AC-FPAA-H3PO4 was synthesized using chemical activation (H3PO4, 4 M) followed by pyrolysis at 600 °C for 1 h and characterized using BET, FTIR, and SEM-EDX. AC-FPAA-H3PO4 exhibited a surface area of 1895.6 m2/g, which allowed for its reuse in 5 consecutive cycles without requiring active site regeneration. The optimal removal efficiency (97.8%) was achieved at pH 2, 298.15 K, 100 rpm, 20 g/L adsorbent dosage, and 200 mg/L ceftriaxone concentration. The adsorption process was described by Langmuir (R2 = 0.9862) and Freundlich (R2 = 0.9833) isotherms, and the kinetics were fitted to the pseudo-second-order model. The adsorption was spontaneous (ΔG = −6.80 kJ/mol) and exothermic (ΔH = −4.43 kJ/mol), with increased randomness at the solid-solution interface (ΔS = 7.69 J/mol K). The adsorbent demonstrated high efficiency in removing ceftriaxone from real water samples, including river water (99.36%) and well water (96.92%). The findings suggest AC-FPAA-H3PO4 is a promising adsorbent for removing ceftriaxone from an aqueous environment.